Image Based Sexual Abuse proclivity and victim blaming - Afroditi Pina; Alisha Bell; Kimberley Griffin; Eduardo Vasquez (Oñati Socio-Legal Series)
Image Based Sexual Abuse (IBSA) denotes the creation, distribution, and/or threat of distribution of intimate images of another person online without their consent. The present study aims to extend emerging research on perpetration of IBSA with the development and preliminary validation for the moral disengagement in IBSA scale, while also examining the role of the dark triad, sadism, and sexism in a person’s likelihood to perpetrate IBSA. One hundred and twenty English speaking participants (76 women, 44 men; mean age=33 years) were recruited via social media. Machiavellianism and psychopathy were found to predict IBSA proclivity, whilst rivalry narcissism predicted greater feelings of excitement and amusement towards IBSA. Moral disengagement predicted IBSA proclivity and blaming the victim. It was also positively related to greater feelings of amusement and excitement towards IBSA. This suggests a distinct personality profile of IBSA perpetrators, and that moral disengagement mechanisms play a role in facilitating and reinforcing this behaviour.